Six-month outcomes of a web-based intervention for users of amphetamine-type stimulants: Randomized controlled trial - Tait, Robert; McKetin, R.; Kay-Lambkin, F.; Carron-Arthur, B.; Bennett, A.; Bennett, K.; Christensen, H.; Griffiths, K. (Journal of Medical Internet Research, 2015)
Background: The use of amphetamine-type stimulants (ATS) places a large burden on health services.Objective: The aim was to evaluate the effectiveness of a self-guided Web-based intervention (“breakingtheice”) for ATS users over 6 months via a free-to-access site.Methods: We conducted a randomized trial comparing a waitlist control with a fully automated intervention containing 3 modules derived from cognitive behavioral therapy and motivation enhancement. The main outcome was self-reported ATS use in the past 3 months assessed at 3- and 6-month follow-ups using the Alcohol, Smoking, and Substance Involvement Screening Test (ASSIST). Secondary outcomes were help-seeking intentions (general help-seeking questionnaire), actual help seeking (actual help-seeking questionnaire), psychological distress (Kessler 10), polydrug use (ASSIST), quality of life (European Health Interview Survey), days out of role, and readiness to change. Follow-up data were evaluated using an intention-to-treat (ITT) analysis with a group by time interaction.Results: We randomized 160 people (intervention: n=81; control: n=79). At 6 months, 38 of 81 (47%) intervention and 41 of 79 (52%) control participants provided data. ATS scores significantly declined for both groups, but the interaction effect was not significant. There were significant ITT time by group interactions for actual help seeking (rate ratio [RR] 2.16; d=0.45) and help-seeking intentions (RR 1.17; d=0.32), with help seeking increasing for the intervention group and declining for the control group. There were also significant interactions for days completely (RR 0.50) and partially (RR 0.74) out of role favoring the intervention group. However, 37% (30/81) of the intervention group did not complete even 1 module.Conclusions: This self-guided Web-based intervention encouraged help seeking associated with ATS use and reduced days out of role, but it did not reduce ATS use. Thus, this program provides a means of engaging with some sections of a difficult-to-reach group to encourage treatment, but a substantial minority remained disengaged.Trial Registration: Australian and New Zealand Clinical Trials Registry: ACTRN12611000947909;https://www.anzctr.org.au/Trial/Registration/TrialReview.aspx?id=343307 (Archived by WebCite athttp://www.webcitation.org/6Y0PGGp8q).URL http://dx.doi.org/10.2196/jmir.3778